PENGARUH KUALITAS PRODUK DAN PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN PRODUK SALAM DI TOKO GEMA FROZEN JOMBANG - Mira Dzurrotun Nasikhah; Lilis Sugi Rahayu Ningsih (CV. ALIM'SPUBLISHING, 2023)
Efforts to create consumer purchasing decisions, the company improves product quality and personal selling so that consumers feel satisfied in using the product and create interest in frozen food products Greetings. Gema Frozen Jombang Store implements product quality by maintaining product resilience and implementing personal selling by interacting directly with consumers. This research aims to determine the effect of Product Quality on Purchase Decisions at Gema Frozen Jombang Stores. This research focuses on consumers at Gema Frozen Jombang stores. The method used in this study is a quantitative research method and the number of samples used is 40 consumers using nonprobability sampling technique. Data collection techniques using a questionnaire. data analysis technique used is descriptive statistics, data quality test, classic assumption test, hypothesis testing and multiple linear regression analysis. Thei results of this study indicate that (1) Product quality has a positive and significant effect on purchasing decisions at Gema Frozen Jombang Stores. (2) Personal Selling has a positive and significant effect on purchasing decisions at Gema Frozen Jombang Stores. (3) Product Quality and Personal Selling have a simultaneous effect on purchasing decisions at Gema Frozen Jombang Stores.